The legal measures to promote the application of appropriate technologies in public administration and the provision of public services - Pasanaga, Apipat (Law for Development Graduate Journal, 2024)
In an era where digital technology plays a pivotal role in the daily lives of citizens, public administration and the provision of public services can no longer avoid adapting to this transformation. The adoption of appropriate technology is essential to enhance efficiency, transparency, and equity in public service delivery. This academic article aims to analyze the role of law in promoting the use of technology in the public sector by examining relevant legal frameworks and concepts in Thailand. It also explores the current situation, systemic challenges, and successful case studies from foreign countries that have effectively integrated technology into public administration. The study is conducted through documentary research, comparative legal analysis, and the synthesis of policy recommendations and legal measures applicable to the Thai context. The findings reveal that despite Thailand’s ongoing efforts to develop public sector technology, five major challenges remain: (1) structural issues within the government’s technology systems, (2) inequitable allocation of budgets, (3) shortage of skilled personnel and digital literacy, (4) outdated legal frameworks that fail to support technological advancement, and (5) digital inequality affecting access among certain population groups. To address these challenges, the article proposes both revisions to existing laws and the enactment of new legislation in line with digital governance. These include establishing minimum standards for electronic services, promoting data security, creating regulatory bodies to oversee governmental technology use, and encouraging public and private sector participation in designing and supervising state technological initiatives. The proposed measures aim to strike a balance between government efficiency and the protection of individual rights, while fostering a transparent, modern, and sustainable public administration in the long term.